Numerical analysis of structural and material solutions for selected retaining walls - Zakrzewska, Aleksandra; Korentz, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Designing retaining structures depends on many factors, primarily the function of the retaining structure and soil conditions. It is not easy to choose the right retaining structure due to the great variety of their structural and material solutions. Preliminary numerical analyses in this case can be very useful.
Keywords: retaining structures; retaining walls; numerical analysis; FEM; konstrukcje oporowe; ściany oporowe; analiza numeryczna; MES